Análisis sobre las barreras sociales y jurídicas que limitan la consolidación de las fuentes de energía no convencionales en La Guajira (Colombia) - Carlos Javier Velásquez-Muñoz; Nellis Meliza Redondo-Moscote (Revista Iberoamericana de Estudios de Desarrollo)
The Mining-Energy Planning Unit of Colombia has indicated that the country must quintuple its power generation capacity over the next fifty years. In this scenario, the department of La Guajira is shown as a strategic territory for the promotion of non-conventional energies; in particular, solar and wind. However, and despite its vocation, this department has not made use of the potential. In the present research, it is identified and described the social and legal barriers that have limited the consolidation of non-conventional energy sources in La Guajira, based on the analysis of normative and doctrinal pieces, as well as studies and reports on regional development. Likert-type interviews with businessmen and semi-structured interviews with ethnic groups settled in the territory were also designed. The conclusions acknowledge the barriers and therefore offer recommendations for overcoming them.